Tatalaksana Pembedahan Fibrous Displasia pada Pasien Remaja dengan Reshaping Mandibula: Laporan Kasus - Pebrian Diki Prestya; Asri Arumsari; Indra Hadikrishna; Sri Suryanti (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: Fibrous dysplasia is a benign developmental disorder that affects the craniofacial bones among the mandibular bones and is characterized by enlargement as a result of bone being replaced by abnormal fibrous tissue growth. Two types, monostotic or polyostotic lesions, cause a progressively expanding bone lamp, producing cosmetic deformities and functional impairments. Frequently occurs in the posterior region of the mandible bone and is usually unilateral. The etiology of Fibrous dysplasia is not clear but is usually associated with genetic factors. The diagnosis of this deformity is based on clinical, radiological, and histopathological examination. Case Report: A 16-year-old male patient came to the Oral and Maxillofacial Department at Hasan Sadikin General Hospital, Bandung, complaining of a lump in his left lower jaw. The patient complained of a lump that had enlarged in the last 7 years, which caused facial asymmetry. Extraoral examination showed facial asymmetry of the mandibular bone; intraoral examination found a lump with a hard consistency, an elevated vestibule, and no ulceration. Computed tomography (CT) imaging showed a solid mass in the left mandibular area with endosteal scalloping. We planned to remove the hyperplastic bone of the mandible with surgical reshaping. Conclusion: Treatment of this case was challenging because the normal anatomic shape of the mandible bone was hard to achieve. In adolescents, facial asymmetry could occur after surgery because they are still in the growth stage. In this case, we were able to obtain a good prognosis for the patient by removing hyperplastic bone and reconstructing facial deformities